PEGylated Luminescent Gold Nanoclusters: Synthesis, Characterization, Bioconjugation, and Application to One‐ and Two‐Photon Cellular Imaging. (28th February 2013) - Oh, Eunkeu; Fatemi, Fredrik K.; Currie, Marc; Delehanty, James B.; Pons, Thomas; Fragola, Alexandra; Lévêque‐Fort, Sandrine; Goswami, Ramasis; Susumu, Kimihiro; Huston, Alan L.; Medintz, Igor L.
<x xml:space="preserve">Abstract</x> Biocompatible, near‐infrared luminescent gold nanoclusters (AuNCs) are synthesized directly in water using poly(ethylene glycol)‐dithiolane ligands terminating in either a carboxyl, amine, azide, or methoxy group. The ≈1.5 nm diameter AuNCs fluoresce at ≈820 nm with quantum yields that range from 4–8%, depending on the terminal functional group present, and display average luminescence lifetimes approaching 1.5 μs. The two‐photon absorption (TPA) cross‐section and two‐photon excited fluorescence (TPEF) properties are also measured. Long‐term testing shows the poly(ethylene glycol) stabilized AuNCs maintain colloidal stability in a variety of media ranging from saline to tissue culture growth medium along with tolerating storage of up to 2 years. DNA and dye‐conjugation reactions confirm that the carboxyl, amine, and azide groups can be utilized on the AuNCs for carbodiimide, succinimidyl ester, and CuI‐assisted cycloaddition chemistry, respectively. High signal‐to‐noise one‐ and two‐photon cellular imaging is demonstrated. The AuNCs exhibit outstanding photophysical stability during continuous‐extended imaging. Concomitant cellular viability testing shows that the AuNCs also elicit minimal cytotoxicity. Further biological applications for these luminescent nanoclustered materials are discussed.